Increasing the Impact of Public Spending on Agricultural Growth : Myanmar Agricultural Public Expenditure Review - World Bank (Washington, DC, 2017)
Agriculture sector growth in Myanmar averaged 2.5 percent during 2009/10–2016/17. This compares to only half of the growth rate in neighboring China and Thailand at the same stage of their economic development and less than one-third of nonagricultural growth in Myanmar. This low agricultural growth is one of the main reasons for slow poverty reduction, high malnutrition, and job insecurity in many parts of Myanmar, given the sector’s continued significance in gross domestic product (GDP) (29 percent), the labor force (50 percent), and exports (30 percent). This first-ever Agricultural Public Expenditure Review is an important step to deepen the policy dialogue on improving the impact of public services on agricultural growth and other developmental objectives. It covers the period from 2009/10 to 2016/17, analyzing the budgets of the Union Ministry of Agriculture, Livestock and Irrigation (MOALI), selected Regions and States, the Myanmar Agricultural Development Bank’s (MADB) financing, and donors. The review focuses on allocative and implementation efficiencies of public expenditures.